Closing the Window on Light Charged Higgs Bosons in the NMSSM. (8th November 2012) - Rathsman, Johan; Rössler, Thomas
Abstract : In the Next-to-Minimal SuperSymmetric Model (NMSSM) the lightest CP-odd Higgs bosons (a 1 ) can be very light. As a consequence, in addition to the standard charged Higgs boson (h ± ) decays considered in the MSSM for a light charged Higgs (m h ± < m t ), the branching fraction forh ± → a 1 W can be dominant. We investigate how this signal can be searched for int t - production at the Large Hadron Collider (LHC) in the case that (m a 1 ≳ 2 m B ) with thea 1 giving rise to a singleb b - -jet and discuss to what extent the LHC experiments are able to discover such a scenario with an integrated luminosity 20 fb −1 . We also discuss the implications of the possible Higgs-signal observed at the LHC.